A chromosome‐level genome assembly of rice leaffolder, Cnaphalocrocis medinalis. (3rd November 2020) - Zhao, Xianxin; Xu, Hongxing; He, Kang; Shi, Zhenmin; Chen, Xi; Ye, Xinhai; Mei, Yang; Yang, Yajun; Li, Meizhen; Gao, Libin; Xu, Le; Xiao, Huamei; et al.
Abstract: The rice leaffolder, Cnaphalocrocis medinalis Guenée (Crambidae, Lepidoptera), is an important agricultural pest that causes serious losses to rice production in rice‐growing regions with high humidity and temperature. However, a lack of genomic resources limits in‐depth understanding of its biological characteristics and ecological adaptation. Here, we sequenced the genome of rice leaffolder using the Illumina and PacBio platforms, yielding a genome assembly of 528.3 Mb with a contig N50 of 524.6 kb. A high percentage (96.4%) of Benchmarking Universal Single‐Copy Orthologs (BUSCOs) were successfully detected, suggesting high‐level completeness of the genome assembly. In total, 39.5% of the genome consists of repeat sequences and 15, 045 protein‐coding genes were annotated. Comparative phylogenomic analysis showed that some gene families associated with hormone biosynthesis expanded in rice leaffolder. Next, we used the Hi‐C technique to produce a chromosome‐level genome assembly with a scaffold N50 of 16.1 Mb by anchoring 3, 248 scaffolds to 31 chromosomes. The rice leaffolder genome showed high chromosomal synteny with the genome of four other lepidopteran insects. By comparing coverage ratios from the genome resequencing of male and female pupae, we identified near intact Z and W chromosomes. The W chromosome is estimated as 20.75 Mb, which is the most complete known W chromosome in Lepidoptera. The protein‐coding genes on the W chromosome were significantly enriched in metabolic pathways. In all, the high‐quality genome assembly and the near‐intact W chromosome of rice leaffolder should be a useful resource for the fields of insect migration, chromosome evolution and pest control.